Case report: Rare persistent complete donor chimerism and GVHD following micro-transplantation from HLA haplotype homozygous donors - Liu, Lingling; Cui, Qingya; Li, Mengyun; Li, Zheng; Chen, Sifan; Ma, Yunju; He, Jun; Wu, Depei; Tang, Xiaowen (Frontiers in Immunology, 2022)
HLA-mismatched hematopoietic stem cell micro-transplantation (MST) is an effective treatment for older patients (≥60 years) with acute myeloid leukemia. Donor selection for MST is broad, ranging from HLA fully mismatched unrelated donors to HLA partially matched related donors. However, the influence of HLA haplotype homozygous donors such donors on MST has not been studied. Such donors has been reported to be associated with a higher risk of graft-versus-host disease (GVHD) in transfusion and cord blood transplantation (CBT). Additionally, sustained complete donor chimerism is rare in MST and usually accompanied by severe acute GVHD and death. Herein, we report the first case of MST using an HLA haplotype homozygous donor. The patient developed persistent complete donor chimerism (donor cells>95%) for 7 months and prolonged isolated thrombocytopenia (PT) for 3 months, after receiving MST from his HLA homozygous son. Grade I acute GVHD presented on day 12 post-MST and it was controlled by timely immunosuppressive treatment. Then he maintained complete molecular remission, complete donor chimerism and mild GVHD for 5 months. However, moderate overlapping GVHD with skin, oral, eyes, and intestinal involvement developed after he self-discontinued Tacrolimus treatment. Fortunately, the GVHD was controlled after intensive anti-rejection therapy and Tacrolimus is now being continued for prophylaxis. This case underscores that HLA haplotype homozygous donors might not be a good choice for MST and GVHD prophylactic should be administrated if such donors have to be selected.